2023
DOI: 10.1002/mp.16434
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Delivery benefit and dosimetric implication of synchrotron‐based proton pencil beam scanning using continuous scanning mode

Abstract: BackgroundDiscrete spot scanning (DSS) is the commonly used method for proton pencil beam scanning (PBS). There is lack of data on the dose‐driven continuous scanning (DDCS).PurposeTo investigate delivery benefits and dosimetric implications of DDCS versus DSS for PBS systems.MethodsThe irradiation duty factor, beam delivery time (BDT), and dose deviation were simulated for eight treatment plans in prostate, head and neck, liver, and lung, with both conventional fractionation and hypofractionation schemes. DDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…DDCS when compared with DSS (Liang et al 2022). In this present study, a comparison between DSS and DDCS irradiation duty factor and BDTs were also conducted, and our results align with previously published work (Liang et al 2022(Liang et al , 2023. The substantial improvement in the irradiation duty factor within DDCS can be attributed to two factors.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…DDCS when compared with DSS (Liang et al 2022). In this present study, a comparison between DSS and DDCS irradiation duty factor and BDTs were also conducted, and our results align with previously published work (Liang et al 2022(Liang et al , 2023. The substantial improvement in the irradiation duty factor within DDCS can be attributed to two factors.…”
Section: Discussionsupporting
confidence: 89%
“…DDCS, through the elimination of beam-offs between spots, holds the potential of improving irradiation duty factor and reducing BDT. Previous research has demonstrated that DDCS substantially improves the irradiation duty factor (range, 11%-41%) compared to DSS (range, 4%-14%) (Liang et al 2023). In our earlier study encompassing 36 clinical plans for 6 treatment sites, an average reduction of 10% in BDT was observed for a BDT is the total beam delivery time, defined as from the instance that the irradiation started to the instance that the last spot finished irradiation.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations